A systematic review of plantar pressure values obtained from male and female football and the test methodologies applied - Husain, E.; Angioi, M.; Mehta, R.; Barnett, D. N.; Okholm Kryger, K. (Footwear Science, 2020)
Football players are at risk of overuse injuries, discomfort and decreased performance due to the boot design and repetitive plantar loading of the sport. However, there is no agreement of normative values for plantar pressure in football or how these should be assessed. Therefore, the aims of this study were to systematically review plantar pressures obtained for male and female adult football players and the methodology applied in the literature. PubMed [MEDLINE], EmBase, Scopus and Web of Science were searched from inception to 19/11/2018 using key terms related to football, plantar, foot and pressure. Two independent reviewers reviewed each paper. Quality of included studies was assessed using The NIH Quality Assessment Tool for Observational Cohort and Cross-sectional studies. Fourteen studies were included, 10 looking at male players, and 4 at both male and female players. Out of the 14 studies, 2 were poor quality, 7 were fair quality and 5 were good quality. Heterogeneity was seen in test setup, assessment method and information provided on external impacting factors. The forefoot region most commonly resulted in the highest pressure in both male and female players, with the highest reported forefoot pressure occurring during side cut in both male (653 ± 131 kPa) and female (492 ± 86 kPa) players. Common pressures for males and females subdivided by movement was summarized. Yet, the heterogeneity in methodology and low number of studies decrease the strength of the data. Therefore, suggestions have been made for future research to improve evidence, and for application of standardized test protocols.